Modified artificial graphite material, preparation method and application thereof, and secondary battery

By wrapping the functionalized carbon composite layer on the surface of the graphite crystal matrix of the artificial graphite material, the problem of difficulty in simultaneously improving the compaction density, capacity and fast charging performance of artificial graphite in the prior art is solved, and efficient electrochemical performance improvement is achieved.

CN119683614AActive Publication Date: 2025-03-25GUANGDONG KAIJIN NEW ENERGY TECH CORP LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411750076.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-25
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The prior art is difficult to improve the compaction density and capacity of artificial graphite while improving its fast charging performance.

Method used

By wrapping the functionalized carbon composite layer on the surface of the graphite crystal matrix, it contains amorphous carbon, carbon surface defects and oxygen-containing functional groups, a moderate disorder is formed to improve the compaction density, capacity and fast charging performance of the material.

Benefits of technology

The high capacity, high compaction density and excellent fast charging performance of modified artificial graphite materials are achieved, meeting the performance requirements of power batteries for capacity, compaction density and fast charging and discharge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683614A_ABST
    Figure CN119683614A_ABST
Patent Text Reader

Abstract

The invention provides a modified artificial graphite material, a preparation method and application thereof, and a secondary battery. The modified artificial graphite material comprises a graphite crystal matrix and a functionalized carbon composite layer wrapping the graphite crystal matrix. The functionalized carbon composite layer includes amorphous carbon, carbon surface defects, and oxygen-containing functional groups. A Raman test shows that the ID / IG peak area ratio in a spectrum is 0.30-0.60, ID represents a D peak at 1350 cm <-1 >, and IG represents a G peak at 1580 cm <-1 >. And the ID / IG peak area ratio in the Raman spectrum is 0.30-0.60, which indicates that the disorder degree of the amorphous carbon is within a certain range, the amorphous carbon can provide more lithium ion diffusion channels to improve the rapid charging and discharging performance under a certain degree, and the influence on the performance of the graphite due to overhigh disorder degree can be avoided. The carbon surface defects can increase the specific surface area to increase the capacity of the material. The functionalized carbon composite layer containing amorphous carbon, carbon surface defects and oxygen-containing functional groups wraps the surface of the graphite crystal matrix, so that the rebound rate can be reduced, and the compaction density can be increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon material preparation, and in particular to a modified artificial graphite material and a preparation method, application and secondary battery thereof. Background Art

[0002] With the widespread promotion of new energy vehicles, the replacement of fuel vehicles by electric vehicles has become an inevitable trend in the development of the industry. As the core component of electric vehicles, the energy density and rate performance of power batteries determine the endurance and fast charging performance of electric vehicles. Therefore, the market has put forward higher and higher requirements on the capacity, compaction density, fast charging and discharging performance of power batteries.

[0003] Graphite is currently the most widely used negative electrode material and one of the important factors affecting the relevant performance of batteries. It has a great impact on the performance of batteries. Graphite is usually divided into artificial graphite and natural graphite. Since natural graphite is relatively soft and compaction easily leads to particle deformation, the industry tends to use artificial graphite more.

[0004] In order to improve the gram capacity, compaction density and fast charging performance of artificial graphite, current commercial products usually adopt the optimization of raw materials, improvement of aggregate particle size and coating to achieve this. Specifically, the capacity and compaction density of the final material are improved by selecting easily graphitized petroleum coke, needle coke or natural graphite; or the fast charging performance of the material is improved by surface coating. Although the above methods can prepare artificial graphite materials with high capacity, high compaction or fast charging, they cannot take into account high capacity, high compaction and fast charging performance at the same time.

[0005] Therefore, how to improve the compaction density and capacity of artificial graphite while improving the fast charging performance is a technical problem that needs to be solved urgently. Summary of the invention

[0006] The purpose of the present invention is to provide a modified artificial graphite material and its preparation method, application and secondary battery. The modified artificial graphite material has a high gram capacity and compaction density, good fast charging performance, simple preparation process, and can be mass-produced to meet the market requirements for the capacity, compaction density, fast charging and discharging performance of power batteries.

[0007] To achieve the above object, the first aspect of the present invention provides a modified artificial graphite material, comprising a graphite crystal matrix and a functionalized carbon composite layer wrapping the graphite crystal matrix, wherein the functionalized carbon composite layer comprises amorphous carbon, carbon surface defects and oxygen-containing functional groups, and the Raman test shows that the spectrum of the modified artificial graphite material is D / I G The peak area ratio is 0.30~0.60, I D Representative is located at 1350cm -1 D peak at I GRepresentative is located at 1580cm -1 The G peak at .

[0008] In the technical solution adopted by the present invention, the modified artificial graphite material includes a graphite crystal matrix and a functionalized carbon composite layer encapsulating the graphite crystal matrix, and the functionalized carbon composite layer contains amorphous carbon, carbon surface defects and oxygen-containing functional groups. D / I G The peak area ratio is 0.30-0.60, indicating that the disorder of amorphous carbon is within a certain range. Amorphous carbon to a certain extent can provide more lithium ion diffusion channels to improve the fast charge and discharge performance, and can also avoid excessive disorder affecting the performance of graphite. Carbon surface defects can increase the specific surface area to increase the capacity of the material. The functionalized carbon composite layer containing amorphous carbon, carbon surface defects and oxygen-containing functional groups wrapped around the surface of the graphite crystal matrix can reduce the rebound rate and increase the compaction density.

[0009] As a technical solution of the present invention, the specific surface area of ​​the modified artificial graphite material is ≥1.20m 2 / g.

[0010] As a technical solution of the present invention, the Dv50 of the modified artificial graphite material is 8.0-16.0 μm.

[0011] As a technical solution of the present invention, the compaction density of the graphite crystal matrix under a pressure of 50000N is D1, the compaction density of the modified artificial graphite material under a pressure of 50000N is D2, and the compaction change rate of the modified artificial graphite is D, wherein D=D2-D1≥0.05g / cm 3 .

[0012] As a technical solution of the present invention, the rebound rate of the modified artificial graphite material is ρ, ρ is 10.0-50.0%, ρ=(P 5t -P 20N ) / P 5t *100, where ρ is the rebound rate, P 5t is the compaction density under a pressure of 50000N, P 20N After unloading the pressure, only the compaction density under 20N pressure is retained.

[0013] As a technical solution of the present invention, the gram capacity of the modified artificial graphite material is ≥350.0 mAh / g, and the 3C / 1C charging capacity retention rate is ≥82.0%.

[0014] The second aspect of the present invention provides a method for preparing a modified artificial graphite material, comprising the steps of:

[0015] ① Graphitizing the carbon source precursor to obtain a first intermediate;

[0016] ② Mechanically crushing the first intermediate to obtain a second intermediate;

[0017] ③ etching the second intermediate with acid to obtain a mixed solution containing the third intermediate;

[0018] ④ Add an oxidant to the mixed solution for oxidation treatment, followed by washing and drying.

[0019] In the preparation method of the present invention, the first intermediate is mechanically crushed so that the graphite surface has a large number of defects to increase the specific surface area of ​​the material, and then the defects of the second intermediate and the graphite edge are etched by acid etching, thereby destroying the long-range ordered crystal structure of the graphite surface and forming a disordered amorphous carbon layer. The purpose of continuing to add an oxidant for oxidation is to further promote the orderly growth of the amorphous carbon layer, and at the same time promote the attachment of oxygen-containing functional groups to the surface of the material to form a functionalized carbon composite layer comprising amorphous carbon, carbon surface defects and oxygen-containing functional groups. Oxidation is performed after acid etching to avoid the oxidant in the acid from enhancing the oxidizability, resulting in too fast a reaction, making it difficult to control the growth of the amorphous carbon layer, affecting the performance of the graphite crystal matrix itself, and may produce more metal residues. Therefore, the present invention forms an artificial functionalized carbon composite layer interface on the graphite surface through a method of mechanical crushing treatment, acid activation and reoxidation, which can improve the compaction density and capacity while also improving the fast charging performance.

[0020] As a technical solution of the present invention, the carbon source precursor can be obtained by crushing, grading and shaping graphitized raw materials, and the graphitized raw materials include at least one of petroleum coke, needle coke and coal tar pitch.

[0021] As a technical solution of the present invention, the graphitization temperature is 2700-3200°C.

[0022] As a technical solution of the present invention, a heat treatment is performed simultaneously with the mechanical pulverization, and the temperature of the heat treatment is 40 to 120°C.

[0023] As a technical solution of the present invention, the mechanical crushing is carried out under an atmosphere, and the atmosphere includes one or more of air, nitrogen and carbon dioxide.

[0024] As a technical solution of the present invention, the processing time of the mechanical crushing is 5 to 120 minutes.

[0025] As a technical solution of the present invention, the equipment used for the mechanical crushing includes one or more of a crusher, a horizontal kettle, a fusion machine, an impact mill, a rod mill, a vertical kettle and a ball mill.

[0026] As a technical solution of the present invention, the equipment used for the mechanical crushing is a crusher, and the host frequency is 5 to 50 Hz.

[0027] As a technical solution of the present invention, the equipment used for the mechanical crushing is an impact mill, and the main engine frequency is 5 to 50 Hz.

[0028] As a technical solution of the present invention, the equipment used for the mechanical crushing is a vertical kettle, and the main engine frequency is 5 to 40 Hz.

[0029] As a technical solution of the present invention, the equipment used for the mechanical crushing is a horizontal kettle, and the main engine frequency is 5 to 50 Hz.

[0030] As a technical solution of the present invention, the equipment used for the mechanical crushing is a fusion machine, and the rotation speed is 100 to 1000 rpm.

[0031] As a technical solution of the present invention, the acid solution used for the acid etching includes one or more of nitric acid, hydrochloric acid and sulfuric acid.

[0032] As a technical solution of the present invention, the concentration of the acid solution used in the acid etching is 1 to 10 mol / L.

[0033] As a technical solution of the present invention, the temperature of the acid etching is 40-100°C.

[0034] As a technical solution of the present invention, the acid etching time is 5 to 20 minutes.

[0035] As a technical solution of the present invention, the solid-liquid ratio of the second intermediate and the acid solution used in the acid etching is 3-300:6-600 kg / L.

[0036] As a technical solution of the present invention, the oxidation treatment is carried out under heating conditions, and the heating temperature is 60-80°C.

[0037] As a technical solution of the present invention, the oxidant includes one or more of potassium dichromate, potassium ferrate, sodium ferrate, potassium permanganate and sodium periodate.

[0038] As a technical solution of the present invention, the mass ratio of the third intermediate to the oxidant is 3-300:1-100.

[0039] As a technical solution of the present invention, the oxidation treatment time is 0.5 to 2.0 hours.

[0040] The third aspect of the present invention provides the use of the modified artificial graphite material prepared according to the aforementioned modified artificial graphite material or the aforementioned method for preparing the modified artificial graphite material in a negative electrode material.

[0041] A fourth aspect of the present invention provides a secondary battery, comprising a positive electrode material, a negative electrode material and an electrolyte, wherein the negative electrode material is the aforementioned modified artificial graphite material, or a modified artificial graphite material prepared by the aforementioned method for preparing the modified artificial graphite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 These are the Raman curves of Example 1 and Comparative Example 1 and Comparative Examples 3-4. DETAILED DESCRIPTION

[0043] The modified artificial graphite material of the present invention is subjected to Raman testing, and the spectrum I D / I G The peak area ratio is 0.30-0.60, where I D Representative is located at 1350cm -1 D peak at I G Representative is located at 1580cm -1 As an example, I D / I G The peak area ratio may be, but is not limited to, 0.30, 0.40, 0.50, or 0.60. D / I G The peak area ratio is moderate, indicating that the disorder degree of the modified artificial graphite material is within a certain range. Amorphous carbon to a certain extent can provide more lithium ion diffusion channels to improve the fast charge and discharge performance, and can also avoid excessive disorder that affects the performance of graphite.

[0044] The gram capacity of the modified artificial graphite material is ≥350.0mAh / g. As an example, it can be, but not limited to, ≥350.0mAh / g, ≥355.0mAh / g, ≥360.0mAh / g, ≥365.0mAh / g, ≥370.0mAh / g, ≥375.0mAh / g, ≥380.0mAh / g, ≥385.0mAh / g, and ≥390.0mAh / g. The 3C / 1C charging capacity retention rate of the modified artificial graphite material is ≥82.0%. As an example, it can be, but not limited to, ≥82.0%, ≥83.0%, ≥84.0%, ≥85.0%, ≥86.0%, ≥87.0%, ≥88.0%, ≥89.0%, ≥90.0%, ≥91.0%, ≥92.0%, ≥93.0%, ≥94.0%, and ≥95.0%. The specific surface area of ​​modified artificial graphite material is ≥1.20m 2 / g, in one embodiment, the specific surface area of ​​the modified artificial graphite material is ≥1.50m 2 / g. As an example, the specific surface area may be, but is not limited to, ≥1.20m 2 / g, ≥1.25m 2 / g, ≥1.30m 2 / g, ≥1.40m 2 / g, ≥1.50m 2 / g, ≥1.60m 2 / g, ≥1.70m 2 / g, ≥1.80m 2 / g, ≥1.90m 2 / g, ≥2.00m 2 / g, ≥2.10m 2 / g, ≥2.20m 2 / g, ≥2.30m 2 / g, ≥2.40m 2 / g, ≥2.50m 2 / g. The Dv50 of the modified artificial graphite material is 8.0-16.0 μm, and as an example, it can be but not limited to 8.0 μm, 9.0 μm, 10.0 μm, 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, 15.0 μm, 16.0 μm. The compaction density of the graphite crystal matrix under a pressure of 50000N is D1, the compaction density of the modified artificial graphite material under a pressure of 50000N is D2, and the compaction change rate of the modified artificial graphite is D, where D=D2-D1≥0.05g / cm 3 The rebound rate of the modified artificial graphite material is ρ, ρ is 10.0~50.0%, ρ=(P 5t -P 20N ) / P 5t *100, as an example, ρ can be but not limited to 10.0%, 15.0%, 20.0%, 25.0%, 30.0%, 35.0%, 40.0%, 45.0%, 50.0%. Where ρ is the rebound rate, P 5t is the compaction density under a pressure of 50000N, P 20N After unloading the pressure, only the compaction density under 20N pressure is retained.

[0045] The modified artificial graphite material includes a graphite crystal matrix and a functionalized carbon composite layer encapsulating the graphite crystal matrix. The functionalized carbon composite layer contains amorphous carbon, carbon surface defects and oxygen-containing functional groups. Among them, the amorphous carbon is obtained by acid etching and oxidation treatment, the carbon surface defects are obtained by mechanical crushing, and the oxygen-containing functional groups are attached to the surface layer by oxidizing the defects on the edges and surfaces of the graphite crystal matrix with an oxidant.

[0046] The preparation method of the modified artificial graphite material of the present invention comprises the following steps: ① graphitizing a carbon source precursor to obtain a first intermediate; ② mechanically crushing the first intermediate to obtain a second intermediate; ③ acid-etching the second intermediate to obtain a mixed solution containing a third intermediate; ④ adding an oxidant to the mixed solution for oxidation treatment, followed by washing and drying.

[0047] Wherein, in step ①, the carbon source precursor can be obtained by crushing, grading and shaping the graphitized raw material, and the graphitized raw material includes at least one of petroleum coke, needle coke and coal tar pitch. The graphitization temperature is 2700-3200°C, and as an example, the temperature can be but not limited to 2700°C, 2800°C, 2900°C, 3000°C, 3100°C, 3200°C.

[0048] In step ②, heat treatment is performed while mechanically pulverizing, and the temperature of the heat treatment is 40 to 120°C. In one embodiment, the temperature of the heat treatment is 60 to 80°C. As an example, the temperature may be, but is not limited to, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 1000°C, 110°C, and 120°C. Mechanical pulverization is performed under an atmosphere, and the atmosphere includes one or more of air, nitrogen, and carbon dioxide. The processing time of mechanical pulverization is 5 to 120 minutes. In one embodiment, the processing time is 20 to 60 minutes. As an example, the processing time of mechanical pulverization may be, but is not limited to, 5 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes, 110 minutes, and 120 minutes.

[0049] The equipment used for mechanical crushing includes one or more of a crusher, a horizontal kettle, a fusion machine, an impact mill, a rod mill, a vertical kettle and a ball mill. For example, if the equipment used for mechanical crushing is a crusher, and the host frequency is 5 to 50 Hz, in one technical solution, the host frequency is 15 to 20 Hz. The equipment used for mechanical crushing is an impact mill, and the host frequency is 5 to 50 Hz. In one technical solution, the host frequency is 20 to 30 Hz. The equipment used for mechanical crushing is a vertical kettle, and the host frequency is 5 to 40 Hz. In one technical solution, the host frequency is 10 to 20 Hz. The equipment used for mechanical crushing is a horizontal kettle, and the host frequency is 5 to 50 Hz. In one technical solution, the host frequency is 10 to 20 Hz. The equipment used for mechanical crushing is a fusion machine, and the rotation speed is 100 to 1000 rpm. In one technical solution, the rotation speed is 500 to 800 rpm.

[0050] In step ③, the acid solution used for acid etching includes one or more of nitric acid, hydrochloric acid and sulfuric acid. The concentration of the acid solution used for acid etching is 1 to 10 mol / L. In a technical solution, the concentration of the acid solution is 3 to 6 mol / L. As an example, the concentration of the acid solution can be, but is not limited to, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L. The acid etching is carried out under heating conditions, and the heating temperature is 40 to 100 ° C. In a technical solution, the heating temperature is 60 to 80 ° C. As an example, the heating temperature can be, but is not limited to, 40 ° C, 50 ° C, 60 ° C, 70 ° C, 80 ° C, 90 ° C, 100 ° C. The time of acid etching is 5 to 20 min. As an example, the time can be, but is not limited to, 5 min, 8 min, 10 min, 13 min, 15 min, 17 min, 19 min, 20 min. The solid-liquid ratio of the second intermediate and the acid solution used in the acid etching is 3-300:6-600 kg / L. As an example, the solid-liquid ratio can be but is not limited to 3:6 kg / L, 3:50 kg / L, 3:100 kg / L, 3:500 kg / L, 100:6 kg / L, 100:50 kg / L, 100:100 kg / L, 100:500 kg / L.

[0051] In step ④, the oxidation treatment is carried out under heating conditions, and the heating temperature is 60 to 80°C. As an example, the heating temperature may be, but is not limited to, 60°C, 65°C, 70°C, 75°C, and 80°C. The oxidant includes one or more of potassium dichromate, potassium ferrate, sodium ferrate, potassium permanganate, and sodium periodate. The mass ratio of the third intermediate and the oxidant is 3 to 300:1 to 100. As an example, as an example, the solid-liquid ratio may be, but is not limited to, 3:1kg / L, 3:5kg / L, 3:50kg / L, 3:100kg / L, 100:1kg / L, 100:5kg / L, and 100:50kg / L. The time of the oxidation treatment is 0.5 to 2.0h. As an example, the time may be, but is not limited to, 0.5h, 0.8h, 1.0h, 1.2h, 1.5h, 1.8h, and 2.0h.

[0052] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.

[0053] Example 1

[0054] This embodiment is a method for preparing a modified artificial graphite material, which includes the following steps.

[0055] ① Crushing, grading and shaping the petroleum coke into a carbon source precursor, graphitizing the carbon source precursor at a temperature of 3000°C to obtain a carbon source precursor with a Dv50 of about 10μm and a specific surface area of ​​≥1.20m 2 / g of the first intermediate.

[0056] ② Place 10 kg of the first intermediate into a pulverizer, heat to 70° C. in an air atmosphere, and mechanically pulverize at a host frequency of 15 Hz for 30 min to obtain a second intermediate.

[0057] ③ Mix 8 kg of the second intermediate and 20 L of 4 mol / L nitric acid solution, place in a water bath and heat to 80°C, and stir evenly for 10 min to obtain a mixed solution containing the third intermediate.

[0058] ④ Add 5 kg of potassium ferrate to the mixed solution, maintain 80° C., and continue to stir evenly for 1.0 h; then wash the product with deionized water and dry it to obtain a modified artificial graphite material.

[0059] Example 2

[0060] This embodiment is a method for preparing a modified artificial graphite material, which includes the following steps.

[0061] ① Crushing, grading and shaping the petroleum coke into a carbon source precursor, graphitizing the carbon source precursor at a temperature of 3000°C to obtain a carbon source precursor with a Dv50 of about 10μm and a specific surface area of ​​≥1.20m 2 / g of the first intermediate.

[0062] ② Place 10 kg of the first intermediate into an impact mill, heat to 70° C. in an air atmosphere, and grind mechanically at a host frequency of 15 Hz for 30 min to obtain a second intermediate.

[0063] ③ Mix 8 kg of the second intermediate and 20 L of 4 mol / L nitric acid solution, place in a water bath and heat to 80°C, and stir evenly for 10 min to obtain a mixed solution containing the third intermediate.

[0064] ④ Add 5 kg of potassium ferrate to the mixed solution, maintain 80° C., and continue to stir evenly for 1.0 h; then wash the product with deionized water and dry it to obtain a modified artificial graphite material.

[0065] Example 3

[0066] This embodiment is a method for preparing a modified artificial graphite material, which includes the following steps.

[0067] ① Crushing, grading and shaping the petroleum coke into a carbon source precursor, graphitizing the carbon source precursor at a temperature of 3000°C to obtain a carbon source precursor with a Dv50 of about 10μm and a specific surface area of ​​≥1.20m 2 / g of the first intermediate.

[0068] ② Place 10 kg of the first intermediate into a fusion machine, heat to 70° C. in an air atmosphere, and mechanically crush at 800 rpm for 30 min to obtain a second intermediate.

[0069] ③ Mix 8 kg of the second intermediate and 20 L of 4 mol / L nitric acid solution, place in a water bath and heat to 80°C, and stir evenly for 10 min to obtain a mixed solution containing the third intermediate.

[0070] ④ Add 5 kg of potassium ferrate to the mixed solution, maintain 80° C., and continue to stir evenly for 1.0 h; then wash the product with deionized water and dry it to obtain a modified artificial graphite material.

[0071] Example 4

[0072] This embodiment is a method for preparing a modified artificial graphite material, which includes the following steps.

[0073] ① Crushing, grading and shaping the petroleum coke into a carbon source precursor, graphitizing the carbon source precursor at a temperature of 3200°C to obtain a carbon source precursor with a Dv50 of about 15μm and a specific surface area of ​​≥0.90m 2 / g of the first intermediate.

[0074] ② Place 10 kg of the first intermediate into a pulverizer, heat to 70° C. in an air atmosphere, and mechanically pulverize at a host frequency of 15 Hz for 30 min to obtain a second intermediate.

[0075] ③ Mix 8 kg of the second intermediate and 20 L of 4 mol / L nitric acid solution, place in a water bath and heat to 80°C, and stir evenly for 10 min to obtain a mixed solution containing the third intermediate.

[0076] ④ Add 5 kg of potassium ferrate to the mixed solution, maintain 80° C., and continue to stir evenly for 1.0 h; then wash the product with deionized water and dry it to obtain a modified artificial graphite material.

[0077] Example 5

[0078] This embodiment is a method for preparing a modified artificial graphite material, which includes the following steps.

[0079] ① Crushing, grading and shaping the petroleum coke into a carbon source precursor, graphitizing the carbon source precursor at a temperature of 3000°C to obtain a carbon source precursor with a Dv50 of about 10μm and a specific surface area of ​​≥1.20m 2 / g of the first intermediate.

[0080] ② Place 10 kg of the first intermediate into a pulverizer, heat to 70° C. in an air atmosphere, and mechanically pulverize at a host frequency of 15 Hz for 30 min to obtain a second intermediate.

[0081] ③ Mix 8 kg of the second intermediate and 10 L of 4 mol / L nitric acid solution, place in a water bath and heat to 80°C, and stir evenly for 10 min to obtain a mixed solution containing the third intermediate.

[0082] ④ Add 2.5 kg of potassium ferrate to the mixed solution, maintain 80° C., and continue to stir and react evenly for 1.0 h; then wash the product with deionized water and dry it to obtain a modified artificial graphite material.

[0083] Example 6

[0084] This embodiment is a method for preparing a modified artificial graphite material, which includes the following steps.

[0085] ① Crushing, grading and shaping the petroleum coke into a carbon source precursor, graphitizing the carbon source precursor at a temperature of 3000°C to obtain a carbon source precursor with a Dv50 of about 10μm and a specific surface area of ​​≥1.20m 2 / g of the first intermediate.

[0086] ② Place 10 kg of the first intermediate into a pulverizer, heat to 70° C. in an air atmosphere, and mechanically pulverize at a host frequency of 15 Hz for 30 min to obtain a second intermediate.

[0087] ③ Mix 8 kg of the second intermediate and 40 L of 4 mol / L nitric acid solution, place in a water bath and heat to 80°C, and stir evenly for 10 min to obtain a mixed solution containing the third intermediate.

[0088] ④ Add 10 kg of potassium ferrate to the mixed solution, maintain 80° C., and continue to stir and react evenly for 1.0 h; then wash the product with deionized water and dry it to obtain a modified artificial graphite material.

[0089] Example 7

[0090] This embodiment is a method for preparing a modified artificial graphite material, which includes the following steps.

[0091] ① Crushing, grading and shaping the petroleum coke into a carbon source precursor, graphitizing the carbon source precursor at a temperature of 3000°C to obtain a carbon source precursor with a Dv50 of about 10μm and a specific surface area of ​​≥1.20m 2 / g of the first intermediate.

[0092] ② Place 10 kg of the first intermediate into a pulverizer, heat to 70° C. in an air atmosphere, and mechanically pulverize at a host frequency of 5 Hz for 30 min to obtain a second intermediate.

[0093] ③ Mix 8 kg of the second intermediate and 20 L of 4 mol / L nitric acid solution, place in a water bath and heat to 80°C, and stir evenly for 10 min to obtain a mixed solution containing the third intermediate.

[0094] ④ Add 5 kg of potassium ferrate to the mixed solution, maintain 80° C., and continue to stir evenly for 1.0 h; then wash the product with deionized water and dry it to obtain a modified artificial graphite material.

[0095] Example 8

[0096] This embodiment is a method for preparing a modified artificial graphite material, which includes the following steps.

[0097] ① Crushing, grading and shaping the petroleum coke into a carbon source precursor, graphitizing the carbon source precursor at a temperature of 3000°C to obtain a carbon source precursor with a Dv50 of about 10μm and a specific surface area of ​​≥1.20m 2 / g of the first intermediate.

[0098] ② Place 10 kg of the first intermediate into a pulverizer, heat to 70° C. in an air atmosphere, and mechanically pulverize at a host frequency of 25 Hz for 30 min to obtain a second intermediate.

[0099] ③ Mix 8 kg of the second intermediate and 20 L of 4 mol / L nitric acid solution, place in a water bath and heat to 80°C, and stir evenly for 10 min to obtain a mixed solution containing the third intermediate.

[0100] ④ Add 5 kg of potassium ferrate to the mixed solution, maintain 80° C., and continue to stir evenly for 1.0 h; then wash the product with deionized water and dry it to obtain a modified artificial graphite material.

[0101] Example 9

[0102] This embodiment is a method for preparing a modified artificial graphite material, which includes the following steps.

[0103] ① The coal tar is crushed, graded and shaped to obtain a carbon source precursor, and the carbon source precursor is graphitized at a temperature of 3000°C to obtain a carbon source precursor with a Dv50 of about 10μm and a specific surface area of ​​≥1.20m 2 / g of the first intermediate.

[0104] ② Place 10 kg of the first intermediate into a pulverizer, heat to 60° C. under a carbon dioxide atmosphere, and mechanically pulverize at a host frequency of 15 Hz for 50 min to obtain a second intermediate.

[0105] ③ Mix 8 kg of the second intermediate and 20 L of 4 mol / L nitric acid solution, place in a water bath and heat to 80°C, and stir evenly for 10 min to obtain a mixed solution containing the third intermediate.

[0106] ④ Add 5 kg of potassium ferrate to the mixed solution, maintain 80° C., and continue to stir evenly for 1.0 h; then wash the product with deionized water and dry it to obtain a modified artificial graphite material.

[0107] Example 10

[0108] This embodiment is a method for preparing a modified artificial graphite material, which includes the following steps.

[0109] ① Crushing, grading and shaping the petroleum coke into a carbon source precursor, graphitizing the carbon source precursor at a temperature of 3000°C to obtain a carbon source precursor with a Dv50 of about 10μm and a specific surface area of ​​≥1.20m 2 / g of the first intermediate.

[0110] ② Place 10 kg of the first intermediate into a pulverizer, heat to 80° C. in an air atmosphere, and mechanically pulverize at a host frequency of 15 Hz for 25 min to obtain a second intermediate.

[0111] ③ Mix 8 kg of the second intermediate and 20 L of 2 mol / L hydrochloric acid solution, place in a water bath and heat to 60°C, and stir evenly for 20 min to obtain a mixed solution containing the third intermediate.

[0112] ④ Add 10 kg of potassium permanganate to the mixed solution, maintain 60° C., and continue to stir and react evenly for 2.0 h; then wash the product with deionized water and dry it to obtain a modified artificial graphite material.

[0113] Comparative Example 1

[0114] This comparative example is a method for preparing an artificial graphite material, comprising the following steps: crushing, grading, and shaping the petroleum coke to obtain a carbon source precursor, graphitizing the carbon source precursor at a temperature of 3000°C, and obtaining a carbon source precursor having a Dv50 of about 10 μm and a specific surface area of ​​≥1.20 m 2 / g of artificial graphite.

[0115] Comparative Example 2

[0116] This comparative example is a method for preparing an artificial graphite material, comprising the following steps: crushing, grading, and shaping the petroleum coke to obtain a carbon source precursor, graphitizing the carbon source precursor at a temperature of 3200°C to obtain a carbon source precursor having a Dv50 of about 15 μm and a specific surface area of ​​≥0.90 m 2 / g of artificial graphite.

[0117] Comparative Example 3

[0118] This comparative example is a method for preparing a modified artificial graphite material, comprising the following steps.

[0119] ① Crushing, grading and shaping the petroleum coke into a carbon source precursor, graphitizing the carbon source precursor at a temperature of 3000°C to obtain a carbon source precursor with a Dv50 of about 10μm and a specific surface area of ​​≥1.20m 2 / g of the first intermediate.

[0120] ② Place 10 kg of the first intermediate into a pulverizer, heat to 70° C. in an air atmosphere, and mechanically pulverize at a host frequency of 15 Hz for 30 minutes to obtain artificial graphite.

[0121] Comparative Example 4

[0122] This comparative example is a method for preparing a modified artificial graphite material, comprising the following steps.

[0123] ① Crushing, grading and shaping the petroleum coke into a carbon source precursor, graphitizing the carbon source precursor at a temperature of 3000°C to obtain a carbon source precursor with a Dv50 of about 10μm and a specific surface area of ​​≥1.20m 2 / g of the first intermediate.

[0124] ② Place 10 kg of the first intermediate into a pulverizer, heat to 70° C. in an air atmosphere, and mechanically pulverize at a host frequency of 15 Hz for 30 min to obtain a second intermediate.

[0125] ③ Mix 8 kg of the second intermediate and 20 L of 4 mol / L nitric acid solution, place in a water bath and heat to 80° C., stir evenly for 10 min, wash with deionized water, and dry to obtain a modified artificial graphite material.

[0126] Comparative Example 5

[0127] This comparative example is a method for preparing a modified artificial graphite material, comprising the following steps.

[0128] ① Crushing, grading and shaping the petroleum coke into a carbon source precursor, graphitizing the carbon source precursor at a temperature of 3000°C to obtain a carbon source precursor with a Dv50 of about 10μm and a specific surface area of ​​≥1.20m 2 / g of the first intermediate.

[0129] ② Place 10 kg of the first intermediate into a pulverizer, heat to 70° C. in an air atmosphere, and mechanically pulverize at a host frequency of 30 Hz for 30 min to obtain a second intermediate.

[0130] ③ Add 20L of deionized water and 5kg of potassium ferrate to the second intermediate, keep the water bath at 80°C, and continue to stir evenly for 1.0h; then wash the product with deionized water and dry it to obtain a modified artificial graphite material.

[0131] Comparative Example 6

[0132] This comparative example is a method for preparing a modified artificial graphite material, comprising the following steps.

[0133] ① Crushing, grading and shaping the petroleum coke into a carbon source precursor, graphitizing the carbon source precursor at a temperature of 3000°C to obtain a carbon source precursor with a Dv50 of about 10μm and a specific surface area of ​​≥1.20m 2 / g of the first intermediate.

[0134] ② Place 10 kg of the first intermediate into a pulverizer, heat to 70° C. in an air atmosphere, and mechanically pulverize at a host frequency of 30 Hz for 30 min to obtain a second intermediate.

[0135] ③ Add 20L of 4mol / L nitric acid solution and 5kg of potassium ferrate to 8kg of the second intermediate, place in a water bath and heat to 80°C, stir evenly to react for 1.0h, then wash the product with deionized water and dry it to obtain a modified artificial graphite material.

[0136] The modified artificial graphite materials or artificial graphites obtained in Examples 1 to 10 and Comparative Examples 1 to 6 were subjected to various performance tests, and the test results are shown in Table 1. The test methods are shown below.

[0137] Raman test: Use Raman spectrometer to test, the spectrum is as follows Figure 1 As shown, I D / I G The value can be obtained through the software on the instrument.

[0138] Particle size Dv50 test: tested using Malvern laser particle size analyzer MS2000.

[0139] Specific surface area test: measured using a Quantachrome surface area tester, NOVA2000e.

[0140] Compaction density test: measured using UTM7305 battery powder compaction density testing machine.

[0141] Half-cell electrical performance test: Prepare a polyvinylidene fluoride solution with a mass fraction of 6-7% using N-methylpyrrolidone as solvent, mix the modified artificial graphite material or artificial graphite, polyvinylidene fluoride, and conductive carbon black prepared in Examples 1-10 and Comparative Examples 1-6 in a mass ratio of 91:7:2, and apply it on copper foil. Put the coated pole piece into a vacuum drying oven at a temperature of 105°C for vacuum drying for 4 hours for standby use, and then punch it into a small disc with a diameter of 14mm. Then transfer it to an argon-filled glove box to assemble a 2430-type button cell, use a three-component mixed solvent of 1mol / L LiPF6 according to EC:DMC:EMC=1:1:1 (volume ratio) as the electrolyte, a metal lithium sheet as the counter electrode, and a 16μm thick diaphragm as the isolation membrane. The assembled half-cell is tested for electrochemical performance on an electrochemical detection system, and the charge and discharge voltage range is 0V to 2.0V, and the charge and discharge gram capacity and 3C / 1C charge capacity retention rate are obtained.

[0142] Table 1 Performance test results of Examples 1 to 10 and Comparative Examples 1 to 6

[0143]

[0144]

[0145] From the results in Table 1, it can be seen that the modified artificial graphite materials of Examples 1 to 10 include a functionalized carbon composite layer comprising amorphous carbon, carbon surface defects and oxygen-containing functional groups, and have a higher gram capacity and compaction density, and their rate performance is also better. This is because the presence of the functionalized carbon composite layer reduces the compaction rebound rate of graphite and provides more lithium ion diffusion channels and reaction active sites, so that its artificial graphite negative electrode material has a higher compaction density and gram capacity, and at the same time has a better rate performance. Comparative Examples 1 to 2 are only artificial graphites obtained by graphitizing carbon source precursors, which do not have disordered amorphous carbon and surface defects, so the performance is poor, especially the 3C / 1C charging capacity retention rate is low. Although mechanical pulverization was performed in Comparative Example 3 to cause defects on the surface of the graphite material, it did not promote the generation of disordered amorphous carbon. Therefore, although the specific surface area has been improved, the rate performance is still poor. Comparative Examples 4 and 5 are single acid etching or oxidation, which can promote the formation of disordered amorphous carbon, but the amorphous carbon formed is limited, so the performance is still worse than that of Example 1. In Comparative Example 6, acid etching and oxidation are carried out simultaneously, and the I of the modified artificial graphite obtained is D / I G The peak area is large because the oxidant will enhance the oxidizability in the acid. The simultaneous oxidation and acid etching will lead to a too fast reaction, making it difficult to control the orderly growth of the amorphous carbon layer. The Raman ID / IG is greater than 0.60, and more metal residues may be produced, thus affecting the electrochemical performance of the battery.

[0146] From the comparison of Examples 1 to 3, it can be seen that when a pulverizer is used for mechanical pulverization, the modified artificial graphite obtained has a larger specific surface area and compaction density, a smaller particle size and rebound rate, a higher degree of disorder of amorphous carbon, and better electrochemical properties of the material. This may be because the pulverizer can obtain a more perfect interface.

[0147] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A modified artificial graphite material, characterized in that: The invention comprises a graphite crystal matrix and a functionalized carbon composite layer wrapping the graphite crystal matrix, wherein the functionalized carbon composite layer comprises amorphous carbon, carbon surface defects and oxygen-containing functional groups, and a Raman test shows that the spectrum of the graphite crystal matrix is D / I G The peak area ratio is 0.30~0.60, I D Representative is located at 1350cm -1 D peak at I G Representative is located at 1580cm -1 The G peak at .

2. The modified artificial graphite material according to claim 1, characterized in that: The specific surface area of ​​the modified artificial graphite material is ≥1.20m 2 / g.

3. The modified artificial graphite material according to claim 1, characterized in that: The Dv50 of the modified artificial graphite material is 8.0-16.0 μm.

4. The modified artificial graphite material according to claim 1, characterized in that: The compaction density of the graphite crystal matrix under a pressure of 50000N is D1, the compaction density of the modified artificial graphite material under a pressure of 50000N is D2, and the compaction change rate of the modified artificial graphite is D, wherein D=D2-D1≥0.05g / cm 3 .

5. The modified artificial graphite material according to claim 1, characterized in that: The rebound rate of the modified artificial graphite material is ρ, ρ is 10.0-50.0%, ρ=(P 5t -P 20N ) / P 5t *100, where ρ is the rebound rate, P 5t is the compaction density under a pressure of 50000N, P 20N After unloading the pressure, only the compaction density under 20N pressure is retained.

6. The modified artificial graphite material according to claim 1, characterized in that: The modified artificial graphite material has a gram capacity of ≥350.0 mAh / g, and a 3C / 1C charging capacity retention rate of ≥82.0%.

7. A method for preparing a modified artificial graphite material, characterized in that: Includes steps: ① Graphitizing the carbon source precursor to obtain a first intermediate; ② Mechanically crushing the first intermediate to obtain a second intermediate; ③ etching the second intermediate with acid to obtain a mixed solution containing the third intermediate; ④ Add an oxidant to the mixed solution for oxidation treatment, followed by washing and drying.

8. The method for preparing the modified artificial graphite material according to claim 7, characterized in that: The invention comprises at least one of the following features (1) to (20): (1) The carbon source precursor can be obtained by crushing, grading and shaping a graphitized raw material, wherein the graphitized raw material includes at least one of petroleum coke, needle coke and coal tar pitch; (2) The graphitization temperature is 2700-3200°C; (3) performing a heating treatment while the mechanical pulverization is performed, wherein the temperature of the heating treatment is 40 to 120° C.; (4) The mechanical pulverization is carried out under an atmosphere, wherein the atmosphere comprises one or more of air, nitrogen and carbon dioxide; (5) The mechanical crushing process lasts for 5 to 120 minutes; (6) The equipment used for the mechanical pulverization includes one or more of a pulverizer, a horizontal kettle, a fusion machine, an impact mill, a rod mill, a vertical kettle and a ball mill; (7) The mechanical crushing device is a crusher, and the main engine frequency is 5 to 50 Hz; (8) The mechanical crushing device is an impact mill, and the main machine frequency is 5 to 50 Hz; (9) The mechanical crushing device is a vertical kettle, and the main engine frequency is 5 to 40 Hz; (10) The equipment used for the mechanical crushing is a horizontal kettle, and the main engine frequency is 5 to 50 Hz; (11) The mechanical crushing device is a fusion machine, and the rotation speed is 100 to 1000 rpm; (12) The acid solution used for the acid etching includes one or more of nitric acid, hydrochloric acid and sulfuric acid; (13) The concentration of the acid solution used in the acid etching is 1 to 10 mol / L; (14) The acid etching temperature is 40 to 100° C.; (15) The acid etching time is 5 to 20 minutes; (16) The solid-liquid ratio of the second intermediate and the acid solution used in the acid etching is 3-300:6-600 kg / L; (17) The oxidation treatment is carried out under heating conditions, and the heating temperature is 60 to 80° C.; (18) The oxidizing agent includes one or more of potassium dichromate, potassium ferrate, sodium ferrate, potassium permanganate and sodium periodate; (19) The mass ratio of the third intermediate to the oxidant is 3-300:1-100; (20) The oxidation treatment time is 0.5 to 2.0 hours.

9. Use of the modified artificial graphite material according to any one of claims 1 to 6, or the modified artificial graphite material prepared by the method for preparing the modified artificial graphite material according to any one of claims 7 to 8, in negative electrode materials.

10. A secondary battery comprising a positive electrode material, a negative electrode material and an electrolyte, characterized in that: The negative electrode material is the modified artificial graphite material described in any one of claims 1 to 6, or the modified artificial graphite material prepared by the method for preparing the modified artificial graphite material described in any one of claims 7 to 8.

Citation Information

Patent Citations

  • Secondary battery, device, artificial graphite, and preparation method therefor

    CN113207314A

  • Modified artificial graphite material, preparation method and application thereof, and lithium ion battery

    CN113233451A

  • Graphite modified material, graphite-based negative electrode active material and preparation method and application thereof

    CN115172743A

  • Method for preparing high-performance lithium ion battery negative electrode material from artificial graphite

    CN115224255A

  • Artificial graphite negative electrode material and preparation method thereof, negative electrode plate and secondary battery

    CN118507719A